Let x + y + z = 1 then:
z + y x + x + z y + x + y z has a minimum value of B A , where A and B are coprime positive integers. What is A + B ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Thank you, nice solution.
Let a 1 = z + y x , a 2 = x + z y , and a 3 = x + y z .
Then by the AM-GM inequality , 3 a 1 + a 2 + a 3 ≥ 3 a 1 a 2 a 3 , and a 1 + a 2 + a 3 has a minimum value when a 1 = a 2 = a 3 . Therefore, z + y x = x + z y = x + y z .
Since x + y + z = 1 , z + y = x − 1 , x + z = y − 1 , and x + y = z − 1 . Substituting these in the above equation, we have a minimum value when x − 1 x = y − 1 y = z − 1 z , so x = y = z .
Since x = y = z and x + y + z = 1 , x = y = z = 3 1 , and the minimum value is z + y x + x + z y + x + y z = 3 1 + 3 1 3 1 + 3 1 + 3 1 3 1 + 3 1 + 3 1 3 1 = 2 3 .
Therefore, A = 3 and B = 2 , and A + B = 5 .
Thank you, nice solution.
Relevant wiki: Jensen's Inequality
First solution :
Let f ( x ) = 1 − x x , f ’ ’ ( x ) > 0 .
Therefore, ∑ 1 − x x ≥ 1 − s 3 s , where s = 3 x + y + z = 3 1 .
By Jensen's inequality: z + y x + x + z y + x + y z ≥ 2 3 .
Second Solution :
z + y x + x + z y + x + y z ≥ 3 1 ( x + y + z ) ( y + z 1 + z + x 1 + x + y 1 )
We know that f ( x ) = x 1 is a convex function. so by Jensen's inequality:
z + y x + x + z y + x + y z ≥ 3 1 ( 3 × 3 2 ( x + y + z ) 1 ) = 2 3 .
Problem Loading...
Note Loading...
Set Loading...
Relevant wiki: Cauchy-Schwarz Inequality
Note that x + y + z = 1 ⟹ x + y = 1 − z , y + z = 1 − x and z + x = 1 − y . Using Hölder's inequality as follows:
( 1 − x x + 1 − y y + 1 − z z ) 3 1 ( 1 − x x + 1 − y y + 1 − z z ) 3 1 ( x ( 1 − x ) + y ( 1 − y ) + z ( 1 − z ) ) 3 1 ≥ x + y + z = 1
Cubing both sides:
( 1 − x x + 1 − y y + 1 − z z ) 2 ( x ( 1 − x ) + y ( 1 − y ) + z ( 1 − z ) ) ≥ 1
⟹ ( 1 − x x + 1 − y y + 1 − z z ) 2 ⟹ y + z x + z + x y + x + y z ≥ x + y + z − ( x 2 + y 2 + z 2 ) 1 ≥ 1 − 3 1 1 = 2 3 ≥ 2 3 By Cauchy-Schwartz inequity: ( x + y + z ) 2 ≤ 3 ( x 2 + y 2 + z 2 ) ⟹ x 2 + y 2 + z 2 ≥ 3 1 Equality occurs when x = y = z = 3 1
Therefore, A + B = 3 + 2 = 5 .